Thermal control for high sensitivity terahertz detection module: Design, simulation and experimental verification - Yantang Hua; Chunlong Liu; Min Zhang; Zhiyong Yang; Richa Hu; Zhenyu Lu; Liang Guo (Case Studies in Thermal Engineering)
Based on the overall configuration characteristics of the terahertz detection module and the thermal environmental conditions during the detection mission, particularly the thermal control challenges such as multiple heat sources, high heat dissipation, and compact internal component installation, an effective thermal control design scheme has been proposed. A comparative analysis of the simulation and thermal balance test results of the terahertz detection module under extreme low and extreme high temperature conditions were conducted. The thermal balance test results indicate that the temperatures of the terahertz detection module's framework and internal components meet the thermal control requirements, with the deviation between simulated and tested temperatures being less than 2.8 °C. This indicates that the thermal analysis of the terahertz detection module is reasonable and effective, and the thermal design is correct and feasible. To address the issues of uneven temperature distribution on the heat dissipation plate and the high local temperature of the compressor unit, an improvement measure has been proposed to fill the lightweight grooves of the module's heat dissipation plate. Simulation analysis shows that this measure is effective to some extent. This research provides an important theoretical foundation and research experience for the thermal design of space probe with multiple heat sources and high heat dissipation.